On Equilibrium in Monopolistic Competition with Endogenous Labor - Alexey Kushnir; Alexander Tarasov; Robertas Zubrickas (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We consider a model of monopolistic competition with several heterogeneous sectors and endogenous labor supply. For low (high) values of the labor supply elasticity, we show that there is always a unique equilibrium. For medium values of the labor supply elasticity, the set of equilibria (if non-empty) can comprise of several equilibria, with the number of equilibria bounded by the number of sectors.
Keywords: D43; L13; 330; labor elasticity; multiple equilibria; stability